2001
DOI: 10.1097/00000542-200108000-00007
|View full text |Cite
|
Sign up to set email alerts
|

A Double-blind, Randomized Comparison of IV Lorazepam versus  Midazolam for Sedation of ICU Patients via  a Pharmacologic Model

Abstract: The pharmacology of intravenous infusions of lorazepam differs significantly from that of midazolam in critically ill patients. This results in significant delays in emergence from sedation with lorazepam as compared with midazolam when administered for ICU sedation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(103 citation statements)
references
References 17 publications
3
93
0
2
Order By: Relevance
“…Midazolam and lorazepam have substantial pharmacokinetic and pharmacodynamic differences in critically ill patients. Barr et al (2001) observed that the pharmacodynamic model can predict the depth of sedation for both midazolam and lorazepam with 76% accuracy. The estimated sedative potency of lorazepam is twice that of midazolam, and the relative amnestic potency of lorazepam is 4-fold.…”
Section: Gabaergic Inhibition In Anesthesiologymentioning
confidence: 98%
See 1 more Smart Citation
“…Midazolam and lorazepam have substantial pharmacokinetic and pharmacodynamic differences in critically ill patients. Barr et al (2001) observed that the pharmacodynamic model can predict the depth of sedation for both midazolam and lorazepam with 76% accuracy. The estimated sedative potency of lorazepam is twice that of midazolam, and the relative amnestic potency of lorazepam is 4-fold.…”
Section: Gabaergic Inhibition In Anesthesiologymentioning
confidence: 98%
“…9). Because the relative concentration decrements for midazolam and lorazepam are not markedly different, the differences in emergence times are primarily due to different pharmacokinetics (Barr et al, 2001). …”
Section: Gabaergic Inhibition In Anesthesiologymentioning
confidence: 99%
“…We standardized the doses of different benzodiazepines by converting all benzodiazepine doses into estimated lorazepam equivalents (Table 1). [17][18] At our center, a standardized CIWA-Ar protocol is used to administer symptom-based benzodiazepines with additional dosages of benzodiazepines administered on the basis of physician clinical judgment. For all patients in the ICU, dexmedetomidine is administered without a bolus and is titrated to a sedation target.…”
Section: Patient Characteristics and Treatmentmentioning
confidence: 99%
“…Lorazepam is a benzodiazepine clinically employed for the treatment of anxiety associated or not with depressive symptoms, as preoperative medication, and also as an anticonvulsant in neonates [1][2][3][4][5]. Lorazepam (7-chloro-5-(2-chlorophenyl)-1,3dihydro-3-hydroxy-2H-1,4-benzodiazepin-2-one) is commercially sold as a racemic mixture of S and R enantiomers.…”
Section: Introductionmentioning
confidence: 99%